2022
DOI: 10.1007/s13178-022-00724-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sexual and Reproductive Health Needs and Associated Barriers of Homeless Young Adults in Urban Ghana: A Qualitative Study

Abstract: Background Homelessness has become a major global and public health challenge, especially in low- and middle-income countries. This phenomenon predisposes young adults to severe psychosocial and health challenges. Aim To explore the sexual and reproductive health needs and behaviours of homeless young adults and challenges in accessing these services. Methods A semi-structured interview guide was used for data collection from in-depth intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A South African study of mobile voluntary counseling and testing (VCT) found higher accessibility in urban areas with most users able to walk to the mobile site [28]. Urbanization may result in the concentration of poverty [1,3], yet only 15 articles (13%) in the review capture the effects of poverty at the structural level on SRHR with most focusing more on individual behaviors and individual or household characteristics [6,18,[29][30][31][32][33][34][35][36][37][38][39][40]. Beyond individual income, urban slum environments function as "spatial poverty traps" in which multiple and reinforcing disadvantages are amplified at the neighborhood level, presenting unique challenges to SRHR, particularly among adolescents [14].…”
Section: Structural Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A South African study of mobile voluntary counseling and testing (VCT) found higher accessibility in urban areas with most users able to walk to the mobile site [28]. Urbanization may result in the concentration of poverty [1,3], yet only 15 articles (13%) in the review capture the effects of poverty at the structural level on SRHR with most focusing more on individual behaviors and individual or household characteristics [6,18,[29][30][31][32][33][34][35][36][37][38][39][40]. Beyond individual income, urban slum environments function as "spatial poverty traps" in which multiple and reinforcing disadvantages are amplified at the neighborhood level, presenting unique challenges to SRHR, particularly among adolescents [14].…”
Section: Structural Environmentmentioning
confidence: 99%
“…Although SRH services are offered in both public and private health facilities, FP service delivery channels are often different in urban areas and gaps exist in service coverage from the public sector [26,54]. Urban-dwelling women and adolescent girls generally prefer private over public facilities due to convenience and timeliness of services as well as more friendly environments and respectful providers, while other women may choose public facilities because they offer free service delivery [26,27,29,55]. Drug shops and pharmacies play an important role in the provision of contraceptives, filling gaps in public sector service coverage in urban areas, particularly for vulnerable and harder-to-reach populations such as young and unmarried women (and men), as they may feel more comfortable at these sites [56].…”
Section: Health Facilities and Service Provision In Urban Settingsmentioning
confidence: 99%
See 1 more Smart Citation